Application of the Concrete-Pictorial-Abstract (CPA) Approach to Improve Elementary Students' Spatial Sense - Ersya Neila Rahma Yulia; Hafiziani Eka Putri (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this research is to find out the increase of the Spatial Sense (SS) in the elementary school students through Concrete Pictorial Abstract (CPA) approach viewed from the Prior Mathematics Ability (PMA). The method was the quasi-experimental with pre-test and post-test design control. The topic focused on geometry involving as many as 119 5th grade students from 2 elementary schools in Karawang. The sample was taken through the purposive sampling technique. The instrument was through the test to measure SS and PMA as well as the non-test to observe the students. Descriptively, the increase of SS in the students through the CPA approach was higher than those who learned with the conventional one. Based on inferential statistic test, the increase of the Spatial Sense towards the medium and low PMA groups reaches a p-value 0.000 and 0.0010.05. It means that the increase of the Spatial Sense through the CPA approach was better. However, the increase of the Spatial Sense towards the high PMA reaches p-value 0.1020.05, showing that there was no significant difference. Thus, CPA approach is considered a good alternative to increase the students' SS on the high, medium, and low PMA for students in the upper grades.